PENGARUH TINGKAT PEMAHAMAN PAJAK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN - Muhamad Hamami NAJIH; Jeny Susyanti; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT               This research was conducted at the SAMSAT Karangploso Office in Karangploso District, Malang Regency. This type of research used in this research is quantitative research. The purpose of this study was to determine the effect of the level of tax understanding and service quality on customer satisfaction. The independent variables used are the level of understanding of tax and service quality, while the dependent variable is customer satisfaction. The sample used in this study were 90 respondents who made tax payments at the SAMSAT Karangploso Office. The data collection technique used a questionnaire. The analysis method used is validity test, reliability test, normality test, classical assumption test, hypothesis test, determination test with the help of SPSS software. The results of this study indicate that the variable level of tax understanding and service quality partially and simultaneously has a positive and significant effect on customer satisfaction.Keywords: customer satisfaction, level of tax understanding, service quality